etude des modalites d'accouchement sur uterus unicicatriciel a l'EHS mere-enfant de laghouat 2019/2020 - Guenou Khedidja; Kaabouche Bouchra; Encadré par : Dr Ouziri (Université Amar Telidji de Laghouat Faculté de Médecine, 2021)
A retro-prospective study of 580 observations of childbirth on a uni-cicatricial uterus made in the Department of Gynecology-Obstetrics at the EHS (Specialized Hospital) Mother - Child of LAGHOUAT over a period of 1 years between December 2019 and December 2020, we was used to assess obstetrical behavior in the face of a scarred uterus. The indication of uterine test arose in 32.75% of parturients in our study with a failure rate of 1.73%. The overall vaginal birth success rate was 2.44%. Cesarean section was necessary for delivery in 19.39% of cases including 98.27% of cases immediately and 1.73% of cases after failure of the dynamic labor test. In our study, we noted no cases of maternal death, but we noted 5 cases of uterine rupture, 07 cases of delivery hemorrhage; 15 cases required postpartum blood transfusion; 4 cases of intestinal obstruction postoperatively and 549 cases with a good and normal maternal prognosis. Maternal morbidity was higher in the vaginal delivery group compared to the upper delivery group. As for the fetal assessment, we recorded 10 neonatal deaths, corresponding to an overall mortality of 1.72%.
(À propos d’une série de 580 cas)
107 p.